2014
DOI: 10.1097/hcr.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

An Expanding Knowledge of the Mechanisms and Effects of Alcohol Consumption on Cardiovascular Disease

Abstract: Over the last 2 decades, observational evidence largely supports an association between light to moderate alcohol consumption (up to 1 drink per day in women and up to 2 drinks per day in men) and a lower risk of cardiovascular disease (CVD), largely driven by a reduction in coronary heart disease. Most studies suggest a nadir in risk in the light to moderate range of alcohol intake, which is then countered by an increase in cardiomyopathy, sudden death, and hemorrhagic stroke at higher drinking levels that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 99 publications
3
56
1
7
Order By: Relevance
“…The contrary seems true for the effect of alcohol consumption, as associations are only found with low-frequency loss, suggesting an influence upon the apical part of the cochlea. Dawes et al [2014] also found an inverse effect of alcohol on hearing loss suggesting alcohol has a protective function on hearing due to complex cardiovascular pathways [Matsumoto et al, 2014]. Concerning other cardiovascular risk factors, we found an effect of systolic blood pressure in low-frequency hearing loss in men, an effect of BMI in low-and high-frequency hearing loss in women and an effect of diabetes mellitus in high-frequency hearing loss in men.…”
Section: Discussionsupporting
confidence: 48%
“…The contrary seems true for the effect of alcohol consumption, as associations are only found with low-frequency loss, suggesting an influence upon the apical part of the cochlea. Dawes et al [2014] also found an inverse effect of alcohol on hearing loss suggesting alcohol has a protective function on hearing due to complex cardiovascular pathways [Matsumoto et al, 2014]. Concerning other cardiovascular risk factors, we found an effect of systolic blood pressure in low-frequency hearing loss in men, an effect of BMI in low-and high-frequency hearing loss in women and an effect of diabetes mellitus in high-frequency hearing loss in men.…”
Section: Discussionsupporting
confidence: 48%
“…Auch proarrhythmogene Wirkungen sowohl in Bezug auf das Auftreten von Vorhofflimmern als auch von ventrikulären Tachykardien sind beschrieben [62,63]. Des Weiteren führt chronischer Alkoholkonsum zu einer Blutdruckerhö-hung und zu einem erhöhten Risiko hä-morrhagischer Schlaganfälle [60,62,64,65]. Die kardioprotektiven Wirkungen der oben genannten Studien bezogen sich alle auf geringe bis mäßige Mengen Alkohol.…”
Section: Alkohol - Negative Wirkungenunclassified
“…A recent study, investigating another alcohol drink (vodka), showed that the effect on PPL is transient and abolished ϳ12 h after alcohol intake (58). Indeed, epidemiological studies indicate that low or moderate consumption of alcohol is associated with lower postprandial TAG concentrations in a white population (75,84), and this may be one, albeit not the sole, mechanism by which low to moderate alcohol consumption is associated with reduced CVD risk (23,31,54).…”
Section: E445 Mediterranean Lifestyle and Lipemiamentioning
confidence: 99%